SSP-JCE Volume 17 - Kabošová Lenka; Čákyová Katarína (Selected Scientific Papers: Journal of Civil Engineering, 2022)
The building industry, like many other industries, is driven to take a significant turn due to the pressing issue of global climate change. The potential in digital technologies and digital design approaches is pushed forward and exploited in architecture, structural, civil, and geotechnical engineering. The challenges such as the overheating of buildings and urban spaces, lack of drinking water, expensive and environment-aggressive building materials, and many more are investigated in more depth in Volume 17 of the Selected Scientific Papers - Journal of Civil Engineering.